2018
DOI: 10.14513/actatechjaur.v11.n4.479
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Filler Orientation and Distribution on the Electrical and Mechanical Properties of Graphene Based Polymer Nanocomposites

Abstract: The aim of my proposed study is to develop an alternative production technique of graphene via in-situ exfoliation of graphite in the hosting polymer matrix. The production process is carried out by an alternative top-down production technique for graphene-based polymer nanocomposites called ‘pressing and folding’ (P&F), via in situ exfoliation of expanded graphite (EG) inside the hosting linear low-density polyethylene (LLDPE) matrix. In this way, the properties of the samples containing different wt % of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It has been observed that in many of the literature studies using similar matrices, [ 62–67 ] the amount of graphene and CNT used in these studies ranges from 1.6 to 3.3 times higher than in the work presented in this article to achieve conductivity values up to 1000 times lower than those shown in Figure 8. As shown in Figure 8, the abrupt increase in the electron conductivity from 10 −12 S/cm (nonmodified polymer matrix) to 10 −5 ‐10 −4 S/cm (nanocomposites), indicates a higher degree of connectivity within the embedded conducting phase, suggesting that electric percolation was attained.…”
Section: Resultsmentioning
confidence: 78%
“…It has been observed that in many of the literature studies using similar matrices, [ 62–67 ] the amount of graphene and CNT used in these studies ranges from 1.6 to 3.3 times higher than in the work presented in this article to achieve conductivity values up to 1000 times lower than those shown in Figure 8. As shown in Figure 8, the abrupt increase in the electron conductivity from 10 −12 S/cm (nonmodified polymer matrix) to 10 −5 ‐10 −4 S/cm (nanocomposites), indicates a higher degree of connectivity within the embedded conducting phase, suggesting that electric percolation was attained.…”
Section: Resultsmentioning
confidence: 78%
“…Each has its advantages and disadvantages discussed in the literature in details [4]. Some researchers reported other methods as well [7][8][9].…”
Section: Introductionmentioning
confidence: 99%